Precursor rigidity engineering enables synergistic regulation of closed pores and graphitic domains for balancing energy and power densities in hard carbon anodes - Qiaofeng Huang; Yiwen Sun; Haoliang Lin; Yuhai Wang; Yifan Sha; Weizhen Fan; Litao Shi; Yu Ying; Xianjian Duan; Chunlei Wu; Guang Shi (Chemical Engineering Journal, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

In-situ interfacial C–S–Zn bonding in N/S co-doped hard carbon anchoring ZnS for durable and fast sodium storage - Lingling Liu; Chuanyue Yang; Tong Wang; Jingwen Sun; Xu Yao; Ning Sheng; Xiansen Tao; Lin Shi; Jingquan Sha (Chemical Engineering Journal, 2026)

Multiphase evolution of the normal fault system on the eastern slope of the Yinggehai Basin, Gulf of Tonkin, South China Sea - Jingshuang Luo; Yougong Wang; Zhaohan Xie; Lin Hu; Gaowei Hu; Peng Sha (Journal of Structural Geology, 2026)

Online proteolysis and specific affinity enrichment of ACE inhibitory peptides on a magnetic nanoplatform from Torreya grandis protein - Kexin Liu; Jiajun Cui; Ke Xu; Jiaqi Zheng; Yixuan Xiao; Lin Chen; Sha Li; Jiyou Yang; Hongying Guo; Xin Wang; Fei Gao; Jie Li; et al. (Food Chemistry, 2026)

Substrate type and structural complexity drive macrobenthic diversity of coral reefs in the South China Sea - Peng-Jin Zhu; Li-Sha Hu; Zhan-Wei Zhao; Hong-Qiang Yang; Min Hui; Ze-Lin Chen; Yun-Wei Dong (Coral Reefs, 2026)

A new sesterterpenoid with β -glucuronidase inhibitory activity from the Cordyceps -colonising fungus Aspergillus versicolour ZJUTE2 - Youmin Ying; Yixian Qiu; Jing Tang; Yuhao Lin; Sha Xu; Jiayue Ni; Yun Zhang; Cuiping Tong; Wei Mao (Natural Product Research, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Integrating stimulation and CO2 storage in natural gas hydrate reservoirs: visualization of CO2-foam fracturing and hydrate self-sealing - Kunlin Ma; Jingsheng Lu; Zhibin Sha; Dongliang Li; Decai Lin; Xiaoya Zang; Deqing Liang (Journal of Cleaner Production, 2026)

Directed synthesis, characterization and rheological properties of an ultrahigh molecular weight acetylated-gellan gum - Yue Ming; Zhuangzhuang Shi; Weilong Wang; Jue Li; Yiting Lin; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Targeting perivascular adipose tissue in vascular aging: innovative translational strategies for disease prevention and monitoring - Peng-Xin Wang; Sha-Qi He; Bei Huang; Zi-Fei Liu; Feng Xu; Jun-Jie Yang; Sai Lu; Hui-Xiang Chen; Ze-Qiang Cai; Ling-Qing Yuan; Xiao Lin (Apoptosis, 2026)

A dual-functional nanomaterial for high-capacity uranium(VI) adsorption and rapid fluorescence detection in water - Sha Yang; Xuanzhe Liao; Zhiyu Hou; Yuxin Zhang; Congcong Ding; Ling Ding; Jun Liao; Lielin Wang; Lin Zhang (Process Safety and Environmental Protection, 2026)

Distribution characteristics, source apportionment and risk assessment of heavy metal pollution in typical redevelopment sites in Jinshan District, Shanghai, China - Cheng Shen; Chenyan Sha; Tianhao He; Zhongchun Yan; Xiurong Chen; Kuangfei Lin; Haichao Chen; Jian Wu; Ye Li; Min Liu (Journal of Environmental Sciences, 2026)

Probiotics as a Therapeutic Strategy for Obesity: New Thoughts on the Stress Response Mechanisms of Probiotics In Vitro and In Vivo - Dingkang Wang; Chao Li; Jingru Ma; Ruijie Xu; Wei Jing; Sha Liu; Xiaomin Sun; Lin Shi; Youfa Wang (Probiotics and Antimicrobial Proteins, 2026)

Targeted external donor dosing in single-stage partial nitritation-anammox: A carbon-efficient control framework sustaining ultrahigh total nitrogen removal - Chengcheng Lin; Yanxiao Wei; Sha Wu; Jiao Jin; Yangkai Liu; Hong Chen; Hanbo Yu; Mohd Fadhil Md Din; Eli Hendrik Sanjaya; Binquan Wang (Process Safety and Environmental Protection, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Engineering compartmentalized utilization of glycerol with glucose for high-level chondroitin production in Corynebacterium glutamicum - Zhuangzhuang Shi; Yue Ming; Jue Li; Yiting Lin; Weilong Wang; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Efficient uranium adsorption performance of TiO2 nanoparticles through the bridging effect of SiO2 and the high selectivity of amidoxime - Sha Yang; Zhengqi Yang; Zhiyu Hou; Jun Liao; Lielin Wang; Congcong Ding; Lin Zhang (Journal of Water Process Engineering, 2026)

Prenatal thallium exposure, cord plasma metabolome, and child neurodevelopment: A prospective birth cohort study - Sha Huang; Chenhui Yang; Ying Li; Gaga Mahai; Ya Xie; Lin Qiu; Yuanyuan Li; Wei Xia; Danhong Wang; Shunqing Xu (Journal of Hazardous Materials, 2026)

Exploring the spoilage mechanism differences of yak and cattle meat during chilled storage: A combined 16S rRNA gene sequencing and non-targeted metabolomics approach - Zhoulin Wu; Sha Zhu; Chunrong Wu; Dawei Jing; Jiamin Zhang; Lin Yang; Xinhui Wang; Yongjie Wang (Food Research International, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

A compensatory OSB self-calibration method for user terminals when real-time PPP services lack precise code bias corrections - Xiaojie Li; Lin Pan; Cancan Wang; Hai Sha; Jinglei Guo; Lu Zhang; Yingying Zhao (Advances in Space Research, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

The association of co-exposure to polycyclic aromatic hydrocarbons and phthalates with surrogate indicators of insulin resistance: a panel study - Sha You; Lin Liu; Min Xiang; Lei Zhao; Wenting Guo; Xiaomin Zhang; Rui Zhu; Liangle Yang (Environmental Geochemistry and Health, 2026)

Genetic analysis of patients with low-frequency non-syndromic hearing loss - Sha Yu; Weitao Li; Xinhao Lin; Liheng Chen; Wenxia Chen; Luo Guo; Yilai Shu (Molecular Genetics and Genomics, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Synthesis of lithium-ion sieves based on electrolytic manganese anode slime: Characterization and its lithium adsorption performance - Jun Luo; Jiancheng Shu; Hongyuan Zhao; Jing Wang; Shaoqin Chen; Huimin Yang; Fan Lin; Sha Zhang; Mengjun Chen; Yong Yang (Chemical Engineering Journal, 2025)

A remote sensing-based paradigm for revealing road ecological impacts in permafrost regions - Qingquan Sha; Jiawei Zhao; Lin Huang; Wei Cao; Jiahui Li; Liangxia Zhang; Yun Wang (Transportation Research Part D: Transport and Environment, 2025)

Catalyzation of chlorine dioxide by manganese dioxide for efficient PAHs removal in industrial soil: New insight from relative reactive oxygen species generation - Xiaojun Hu; Qiying Li; Xuhan Lin; Bo Cheng; Zhiwen Cheng; Xuehong Yuan; Jinju Hou; Cheng Shen; Chenyan Sha; Fuwen Liu (Journal of Environmental Chemical Engineering, 2025)

A critical review of oxygen supply and control strategies in single-stage partial nitritation-anammox system for autotrophic nitrogen removal from wastewater - Sha Wu; Fei Gao; Chengcheng Lin; Yijie Quan; Yanxiao Wei; Zhihua Liu; Hanbo Yu; Eli Hendrik Sanjaya; Mohd Fadhil Md Din; Hong Chen (Journal of Environmental Chemical Engineering, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Charge/conformation-transformable phosphopeptide@hollow covalent organic frameworks as molecular gates for electrochemical analysis - Lin Wang; Minghui Wang; Gaoxiang Wang; Haojie Xie; Yu Hang; Dongmei Zhang; Sha Zhu; Xiafei Hu; Genxi Li (Chemical Engineering Journal, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Identification of novel strain Acinetobacter baumannii H1 and its improvement capacity for nutrient removal after coimmobilized on activated carbon and CaCO3 in real aquaculture wastewater - Yonghao Ma; Hu Shu; Huijie Lu; Jiayi Zhou; Jichen Zhao; Fengkun Liu; Yuting Liu; Xunheng Lai; Junduo Lin; Qiang Guo; Sha Yue; Wen Huang (Environmental Research, 2025)

Real-traffic emissions of CO, NOx, CO2, and PM2.5 from vehicles using a portable emission measurement system - Chunying Lu; Shuwei Dong; Shanqian Huang; Shuohan Gao; Jinsheng Fu; Xinyi Tian; Sha Lin; Xinzhu Xiong; Xinjun Wang; Xinfeng Wang (Air Quality, Atmosphere & Health, 2025)

Chitosan/MXene/ε-polylysine based biodegradable packaging films with synergistic photothermal antimicrobial properties - Jia Sha; Zhanpeng Zhu; Mibin Lin; Liang Zhu; Zhaomei Wang; Kaijun Xiao (Food Packaging and Shelf Life, 2025)

Modeling electron competition and pH factor interactions improve cognitions of nitrite accumulation during denitrification - Xuehai Yue; Fengjun Yin; Hao Tan; Junxi Liu; Lin Chang; Xiaohui Yang; Sha Wang; Ying Zhao; Haofei Shi; Wei Zhang; Hong Liu (Environmental Research, 2025)

Degradable microplastics induce more soil organic carbon loss via priming effects: a viewpoint - Zhenyu Yang; Ying Sha; Amit Kumar; Zhiguo Yu; Junjie Lin; Yan Lei (Plant and Soil, 2025)

Fungal Infections in Transplant Recipients Pre- and Post-coronavirus Disease 2019: Results from a Single-Center Retrospective Cohort Study - Tengteng Xin; Qinling Pan; Jiahao Li; Jing Zhang; Li Lin; Kitman Choi; Wenying Cai; Sha Lu; Junmin Zhang (Mycopathologia, 2025)

Beneficial impact of MTGase-modified fish gelatin on collagen supplementation in rats: Insights from serum metabolomics and gut microbiota - Chun-Yan Peng; Ting Fang; Hao-Bin Lin; Ni Zhang; Zi-Zi Hu; Hai-tao Wang; Ming-Hui Su; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2025)

SYMRK significantly affected AMF symbiosis and plant growth in maize - Jing Zhou; Sha Lin; Xinhao Luo; Lixue Sun; Jin Chen; Beijiu Cheng; Xiaoyu Li (Plant Science, 2025)

Biogeographic dynamics of graptolites during the Late Ordovician Mass Extinction in South China - Lin-Na Zhang; Sha-Sha Sun; Zong-Yuan Sun; Ming-Feng Lu; Qing Chen (Palaeoworld, 2025)

Highly sensitive aggregation-induced electrochemiluminescence sensor for cadmium detection in Ganoderma lucidum - Zhi-Hong Xu; Xin Weng; Sha-Sha Wang; Ze-Hao Huang; Wen Xu; Wei Xu; Yu Lin; Hang Gao (Food Chemistry, 2025)

Investigation on coupling of reaction and separation in single catalytic packing packet - Xiaonan Liu; Zheng Lin; Guanyu Pu; Yong Sha (Chemical Engineering Journal, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

Improvement of stability and antioxidant capacity of peptide - iron complexes by sonication - Dong Lin; Yongqing Zhang; Qinqin Xiong; Liyun Zhang; Sha Cheng; Jia Yu; Mashaal Ahmad; Yalin Ni; Su Xu; Heng Luo (Food Chemistry, 2025)

Synthesis and characterization of fish gelatin hydrogels for enhanced biopolymer applications - Wen-Long Cheng; Shan Shan; Sheng Shu; Guang-Xian Liu; Lin-Feng Yuan; Xiao-Mei Sha; Zong-Cai Tu (Food and Bioproducts Processing, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Forest structure predicts aboveground biomass better than community-weighted mean of traits, functional diversity, topography, and soil in a tropical forest across spatial scales - Tim Simmavong; Yuebo Su; Yun Deng; Bin Wang; Zhiliang Yao; Junjie Wu; Liqing Sha; Min Cao; Luxiang Lin (Forest Ecology and Management, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

Evolutionary history and population dynamics of a widespread mantis shrimp Oratosquilla oratoria: Evidence from mitogenomic analysis and species distribution modeling - Liwen Zhang; Lin He; Min Hui; Zhongli Sha; Jiao Cheng (Regional Studies in Marine Science, 2025)

One-step microwave method synthesis of N, S-codoped carbon with the frustrated Lewis pairs for Cr (VI) removal - Liwen Wang; Yixin Sha; Changjun Bi; Daoqing Lin; Yuxue Liu; Lichun Dai; Xiaozhi Wang; Hui Lin; Jawad Ahmad Jrar; Jianhua Hou (Journal of Water Process Engineering, 2025)

Molecular characterization of extended-spectrum β-lactamases from the Akkermansia genus - Jiafu Lin; Tiantian Wang; Yaliang Zhou; Jingzhou Sha; Xueke Chen; Wenjie Wang; Chuan Zhang; Feng Xie; Yiwen Chu; Xinrong Wang; Dan Luo; Tao Song (International Journal of Food Microbiology, 2025)

Enhancing the application of probiotics in probiotic food products from the perspective of improving stress resistance by regulating cell physiological function: A review - Dingkang Wang; Ruijie Xu; Sha Liu; Xiaomin Sun; Tianxiao Zhang; Lin Shi; Youfa Wang (Food Research International, 2025)

Unveiling the susceptibility mechanism of Microcystis to consecutive sub-lethal oxidative stress—Enhancing oxidation technology for cyanobacterial bloom control - Fang Bai; Jie Li; Tianli Li; Jun Sha; Jin Liu; Lin Li; Guofei Dai; Yunlu Jia; Lirong Song (Journal of Hazardous Materials, 2024)

Source-oriented health risk assessment and priority control factor analysis of heavy metals in urban soil of Shanghai - Cheng Shen; Shenfa Huang; Min Wang; Jian Wu; Jinghua Su; Kuangfei Lin; Xiurong Chen; Tianhao He; Ye Li; Chenyan Sha; Min Liu (Journal of Hazardous Materials, 2024)

Role of pyrochar amendment toward carbon neutrality of rice paddy field by mitigating methane emission: A global evaluation by meta-analysis - Xinran Liu; Shuai Yin; Shuhan Xu; Jian Lin; Chengming Zhang; Linkui Cao; Qingnan Chu; Zhimin Sha (Field Crops Research, 2024)

Occurrence, spatial distribution, and ecological risk of benzotriazole UV stabilizers (BUVs) in sediments from Bohai sea of China - Xing Liu; Xiaodan Pei; JiaoJiao Li; Yawen Wei; Hao Sun; Zilan Wu; Sha Wang; Jianmin Chen; Zhongsheng Lin; Ziwei Yao (Environmental Research, 2024)

Genomics‐Informed Range Predictions Under Global Warming Reveal Reduced Adaptive Diversity Whilst Buffering Range Shifts for a Marine Snail - Xiao‐Nie Lin; Chao‐Yi Ma; Li‐Sha Hu; Ming‐Ling Liao; Lin‐Xuan Ma; Peter R. Teske; Ary Hoffmann; Yun‐Wei Dong (Global Change Biology, 2024)
Understanding the genetic basis of local adaptation in thermal performance is useful for predicting species distribution shifts under anthropogenic climate change. Many species are distributed across multiple biogeographic regions, and the uniquely adapted populations in each region may respond to future ocean warming with distinct distribution changes. In the present study, we investigated phylogeographic patterns, thermal sensitivity, and genetic differentiation in the intertidal snail Littorina brevicula along China's coast. Whole‐genome sequencing results based on a newly assembled chromosome‐level genome revealed two genetic lineages, with a north–south divergence that is linked to the thermal environment. Within each lineage, individuals could be further subdivided into genetic subgroups that differ at key genomic loci underpinning differences in upper heat tolerance. Heat stress drives adaptive divergence across multiple levels of organization, from the individual to the biogeographic level. Taking into account genetic diversity associated with variation in heat tolerance, a physiological species distribution model (pSDM) was applied to predict the distributions of the different genetic subgroups in response to climate change. Both northern and southern lineages were predicted to experience declines in habitat suitability under a 4°C future warming scenario, and that a genotypic subset of snails from the southern lineage may even be driven to extinction. These findings illustrate that even when a species' range is maintained, it can nonetheless experience a significant decrease in adaptive diversity as a result of climate change. The integrated approach presented here, which considered both physiological and adaptive genetic variation at the level of individuals within a biogeographical context, provided new insights into how marine species can respond to global warming.

Carbon nanomaterials-based smart dual-mode sensors for colorimetric and fluorescence detection of foodborne hazards - Feifei Sun; Peiran Li; Guojian Wu; Fengjiao He; Sha Liu; Yizhong Shen; Yongning Wu; Lin Li (Trends in Food Science & Technology, 2024)

Benzotriazole ultraviolet absorbents in surface waters and sediments of the Bohai Sea and North Yellow Sea: Spatial trends and influencing factors - Xing Liu; Zilan Wu; Xiaodan Pei; Tian Lin; Jiaojiao Li; Sha Wang; Zhigang Guo; Ziwei Yao (Science of The Total Environment, 2024)

Exploring characteristics of waxy wheat starches cross-linked at low levels: Insights from pasting, rheological, and textural properties - Zhonghua Gu; Xianying Sha; Xinwei Wang; Renyong Zhao; Reham Khashaba; Jay-lin Jane; Hongxin Jiang (Food Bioscience, 2024)

Switchable transformation of biomass-derived furfural to furfuryl alcohol and isopropyl furfuryl ether over a zirconium-based bifunctional catalyst - Lei Hu; Baogang Sha; Yingxuan Shi; Na Shen; Minhui Yang; Keru Chen; Zhen Wu; Xing Tang; Aiyong He; Lu Lin (Chemical Engineering Journal, 2024)

Engineering Au-Pt atomic alloy cocatalysts for enhanced H2 production from photo-reforming of lignocellulosic biomass wastes - Fangjie Ding; Hongbo Yu; Renyong Tu; Sha Li; Lin Chen; Bing Li; Jianzhong Guo; Chunzheng Wu (Chemical Engineering Journal, 2024)

Sinensetin Inhibits Angiogenesis in Lung Adenocarcinoma via the miR-374c-5p/VEGF-A/VEGFR-2/AKT Axis - Tao Ji; Lin Ye; Erping Xi; Ying Liu; Xiumei Wang; Sha Wang (Cell Biochemistry and Biophysics, 2024)

Knockdown of NUF2-derived exosomes can inhibit the migration and autophagy of BC cells and improve resistance to doxorubicin - Lin Luo; Tong Sha; Hongtao Li (Tissue and Cell, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Self-adaptive and soft-contact ellipsoidal pendulum-structured triboelectric nanogenerator for harvesting water wave energy - Bingqi Zhao; Yong Long; Tianci Huang; Jianan Niu; Yuxiu Liu; Wei Sha; Jiangwen Wang; Zhong Lin Wang; Junyi Zhai; Weiguo Hu (Chemical Engineering Journal, 2024)

Structure regulation of lignin-derived N-doped carbon-supported Ni catalyst for efficient upgrading of ethanol to higher alcohols - Quanzhou Xu; Xing Fei; Xueqing Qiu; Xiaofei Wang; Tiejun Wang; Xuliang Lin; Sha Li; Yanlin Qin (Chemical Engineering Journal, 2024)

Metagenomic Next-Generation Sequencing Contributes to the Early Diagnosis of Mixed Infections in Central Nervous System - Li Lin; Junyue Fang; Jiahao Li; Ying Tang; Tengteng Xin; Nengtai Ouyang; Wenying Cai; Lisi Xie; Sha Lu; Junmin Zhang (Mycopathologia, 2024)

miR-141-3p Regulates the Proliferation and Apoptosis of Endometrial-Myometrial Interface Smooth Muscle Cells in Adenomyosis Via JAK2/STAT3 Pathway - Sirui Wang; Hua Duan; Sha Wang; Zhengchen Guo; Qi Lin (Biochemical Genetics, 2024)

Comprehensive assessment of the microbial community structure in a typical lead–zinc mine soil - Taotao Zeng; Haichao Sha; Qingqing Xie; Yue Lu; Haidu Nong; Liangqin Wang; Lin Tang (Environmental Science and Pollution Research, 2024)

The association between per-/polyfluoroalkyl substances in serum and thyroid function parameters: A cross-sectional study on teenagers living near a Chinese fluorochemical industrial plant - Lin-Na Xie; Xiao-Chen Wang; Li-Qin Su; Sai-Sai Ji; Wen Gu; Holly Barrett; Xiao-Jie Dong; Hui-Juan Zhu; Sha-Sha Hou; Zhen-Huan Li; Yi-Lin Liu; Ling Zhang; et al. (Science of The Total Environment, 2024)

Discussion of “Abbas, F. M., & Tanaka, N. (2022). Investigation of flow structure with moat acting as a water cushion at the toe of an overflowing levee. Environmental Fluid Mechanics, 22(4), 865–889.” - Xiaoming Zhu; Lin Zhang; Qiliang Yuan; Sha Shi; Jing Si (Environmental Fluid Mechanics, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

In vitro digestion and fecal fermentation of selenocompounds: impact on gut microbiota, antioxidant activity, and short-chain fatty acids - Shuojia Liang; Junlei Yu; Meng Zhao; Sha Chen; Xiang Lu; Fayin Ye; Jia Chen; Guohua Zhao; Lin Lei (Food Research International, 2024)

Influence of bionics shark gills tunnel portal on the micro-pressure wave at the tunnel exit - Tong-tong Lin; Ming-zhi Yang; Lei Zhang; Tian-tian Wang; Sha Zhong (Tunnelling and Underground Space Technology, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Tinea Capitis Combined with Tinea Vellus in a 4-year-old Boy - Jiahao Li; Wenying Cai; Li Lin; Guiquan Lu; Xinzhe Xie; Sha Lu (Mycopathologia, 2024)

Effects of combined polystyrene nanoplastics and ibuprofen on the activated sludge processes: Short-term exposure in pure cultures versus long-term stress in mixed communities - Daying Chen; Mengxiao Li; Yang Li; Sha Long; Ximing Sun; Hongzhi Geng; Meilin Yin; Yongkui Yang; Lin Zhao (Journal of Water Process Engineering, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Fabrication of a novel gas diffusion electrode (g-C3N4/CB/PTFE-GF) for electro-Fenton treatment of amaranth dye - Daying Chen; Hongzhi Geng; Pengfei Hou; Yihan Li; Sha Long; Meilin Yin; Xiaohui Wang; Lin Zhao (Journal of Water Process Engineering, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Activation of estrogen-related receptor: An alternative mechanism of hexafluoropropylene oxide homologs estrogenic effects - Lu Chen; Xicha Lin; Sha Shi; Minjie Li; Monika Mortimer; Wendi Fang; Fangfang Li; Liang-Hong Guo (Science of The Total Environment, 2023)

Responses of bacterial community composition and diversity to multi-level nitrogen addition at different periods of growing season driven by conditional rare taxa in an alpine meadow - Yilun Hu; Hasbagan Ganjurjav; Guozheng Hu; Guoxu Ji; Lin Han; Yubao Sha; Yan Liang; Qingzhu Gao (Biology and Fertility of Soils, 2023)

Primary cutaneous cryptococcosis presenting as ulcers in solid organ transplant recipient - Ying Tang; Wenying Cai; Li Lin; Jiahao Li; Hsingmei Liu; Liyan Xi; Sha Lu (Mycopathologia, 2023)

Epidemiology and Clinical Findings of Tinea Capitis: A 23-Year Retrospective, Single-Center Study in Guangzhou, China - Wenying Cai; Junhao Huang; Jiahao Li; Li Lin; Liyan Xi; Junmin Zhang; Xiqing Li; Zhen Zhou; Ying Tang; Hsingmei Liu; Jing Zhang; Sha Lu (Mycopathologia, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Recent advances in cellulosic materials for aqueous zinc-ion batteries: An overview - Long Cheng; Yang Huang; Sha Yin; Ming Chen; Yihong Liu; Yidan Zhang; Farzad Seidi; Zixia Lin; Huining Xiao (Carbohydrate Polymers, 2023)

Berberine inhibits gluconeogenesis in spontaneous diabetic rats by regulating the AKT/MAPK/NO/cGMP/PKG signaling pathway - Ming Lu; Yanpeng Wang; Yuanye Jiang; Cuiping Zhang; Hongping Wang; Wenjun Sha; Lin Chen; Tao Lei; Limei Liu (Molecular and Cellular Biochemistry, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Sn2+/Mn2+ co-doped germanate glass with quasi-sunlight spectrum visible-emission and its high-quality w-LED application - Yuhang Zhang; Baojiu Chen; Xizhen Zhang; Yongze Cao; Jinsu Zhang; Sai Xu; Xiangping Li; Hongquan Yu; Duan Gao; Xuezhu Sha; Li Wang; Xin Chen; et al. (Chemical Engineering Journal, 2023)

Polycrystalline ZSM-5@Beta core–shell composites fabricated by a seed-directed approach: A catalyst to boosting light olefin production by ordered hierarchical cracking - Lei Han; Ruoyu Wang; Peng Wang; Yuchen Sha; Aiguo Zheng; Qiuqiao Jiang; Mudi Xin; Haitao Song; Wei Lin (Fuel, 2023)

Revisiting the role of firm-level carbon disclosure in sustainable development goals: Research agenda and policy implications - Beiling Ma; Sha Lin; Muhammad Farhan Bashir; Huaping Sun; Mahwish Zafar (Gondwana Research, 2023)

How does Fintech affect green innovation of Chinese heavily polluting enterprises? The mediating role of energy poverty - Lixia Wang; Yingqian Gu; Lin Sha; Fangyuan Guo (Environmental Science and Pollution Research, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

Quantifying tree canopy coverage threshold of typical residential quarters considering human thermal comfort and heat dynamics under extreme heat - Yingnan Li; Dongli Lin; Yuhan Zhang; Zipeng Song; Xiaohan Sha; Siqi Zhou; Cen Chen; Zhaowu Yu (Building and Environment, 2023)

Interannual variation of summer sea surface temperature in the Amundsen Sea, Antarctica - Lu-Sha Yu; Hailun He; Hengling Leng; Hailong Liu; Pengfei Lin (Frontiers in Marine Science, 2023)
This paper investigates the interannual variability of January sea surface temperature (SST) in the Amundsen Sea (AS) during the period 1982–2022. SST in the Pine Island Bay (PIB) is found to exhibit the most significant interannual variation, with a standard deviation up to 0.6°. Composite analysis indicates that, in warmer years, the January SST at PIB is approximately 1° higher on average than that in cooler years, and its variation in warmer (cooler) years corresponds to lower (higher) sea ice concentration (SIC) and more (less) surface heat flux; the latter factor is primarily influenced by the albedo of SIC. Further analysis suggests that variability in January SIC is largely dominated by northward sea ice motion during the previous November (r = −0.82), which is consistent with the presence of a contemporaneous northerly 10 m wind anomaly trigged by the Amundsen Sea Low (ASL). The ASL-associated northerly wind anomaly drives northward sea ice motion, reduces SIC, and thus increases the downward heat flux that ultimately results in warmer SST, and vice versa. This study identifies the possible mechanism of anomalous January SST in the PIB, which could provide an important clue for seasonal forecasts of summer SST in the AS.

The runoff changes are controlled by combined effects of multiple regional environmental factors in the alpine hilly region of Northwest China - Yafan Zuo; Jianhong Chen; Sha Lin; Kangning He (Science of The Total Environment, 2023)

Designing direct redox reaction chemically coupling NO and SO2 removal - Dongyue Zhao; Qiuqiao Jiang; Bo Peng; Jun Liu; Ruoyu Wang; Menglong Feng; Shangcong Sun; Hao Sha; Kai Zhu; Haitao Song; Wei Lin; Zhijian Da (Fuel, 2023)

In-situ synthesis of covalently-bonded SnS2/FeS2 heterostructures for high rate sodium storage - Hewen Dong; Xixi Wang; Jun Jiang; Wanying Lin; Enzuo Liu; Jianli Kang; Chunsheng Shi; Junwei Sha; Biao Chen; Liying Ma (Chemical Engineering Journal, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Effect of empirical antifungal treatment on mortality in non-neutropenic critically ill patients: a propensity-matched retrospective cohort study - Yue Tang; Wenjing Hu; Shuangyan Jiang; Maoyu Xie; Wenying Zhu; Lin Zhang; Jing Sha; Tengfei Wang; Min Ding; Juan Zeng; Jinjiao Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Generating phone-quality records to train machine learning models for smartphone-based earthquake early warning - Zengwei Zheng; Jiquan Wang; Lifei Shi; Sha Zhao; Jianmin Hou; Lin Sun; Lin Dong (Journal of Seismology, 2022)

Unraveling the Dynamic Integration of Auxin, Brassinosteroid and Gibberellin in Early Shade-Induced Hypocotyl Elongation - Sha Huang; Chuanwei Yang; Lin Li (Phenomics, 2022)

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

Tourism-oriented comprehensive land development (TOLD) in subtropical mountain region, Fuzhou, China - Xiaomei Li; Yun Wu; Jinming Sha; Qixin Lin; Ahmed Eladawy (Arabian Journal of Geosciences, 2022)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

Local 3D scene fine detection analysis of circular landform on the southern edge of Dinosaur Valley - Gao Sha; Yuan Xiping; Gan Shu; Yang Milong; Hu Lin; Bi Rui (Arabian Journal of Geosciences, 2021)

Occurrence of heavy metals, antibiotics, and antibiotic resistance genes in different kinds of land-applied manure in China - Jiajia Xue; Jianqiang Wu; Yaru Hu; Chenyan Sha; Shijie Yao; Peng Li; Kuangfei Lin; Changzheng Cui (Environmental Science and Pollution Research, 2021)

Traits, strategies, and niches of liana species in a tropical seasonal rainforest - Qi Liu; Frank J. Sterck; Jiao-Lin Zhang; Arne Scheire; Evelien Konings; Min Cao; Li-Qing Sha; Lourens Poorter (Oecologia, 2021)
Plant functional traits and strategies hold the promise to explain species distribution, but few studies have linked multiple traits to multiple niche dimensions (i.e., light, water, and nutrients). Here, we analyzed for 29 liana species in a Chinese tropical seasonal rainforest how: (1) trait associations and trade-offs lead to different plant strategies; and (2) how these traits shape species’ niche dimensions. Eighteen functional traits related to light, water, and nutrient use were measured and species niche dimensions were quantified using species distribution in a 20-ha plot combined with data on canopy gaps, topographic water availability, and soil nutrients. We found a tissue toughness spectrum ranging from soft to hard tissues along which species also varied from acquisitive to conservative water use, and a resource acquisition spectrum ranging from low to high light capture and nutrient use. Intriguingly, each spectrum partly reflected the conservative–acquisitive paradigm, but at the same time, the tissue toughness and the resource acquisition spectrum were uncoupled. Resource niche dimensions were better predicted by individual traits than by multivariate plant strategies. This suggests that trait components that underlie multivariate strategy axes, rather than the plant strategies themselves determine species distributions. Different traits were important for different niche dimensions. In conclusion, plant functional traits and strategies can indeed explain species distributions, but not in a simple and straight forward way. Although the identification of global plant strategies has significantly advanced the field, this research shows that global, multivariate generalizations are difficult to translate to local conditions, as different components of these strategies are important under different local conditions.

EEG-Based Anxious States Classification Using Affective BCI-Based Closed Neurofeedback System - Chao Chen; Xuecong Yu; Abdelkader Nasreddine Belkacem; Lin Lu; Penghai Li; Zufeng Zhang; Xiaotian Wang; Wenjun Tan; Qiang Gao; Duk Shin; Changming Wang; Sha Sha; et al. (Journal of Medical and Biological Engineering, 2021)

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

CXCL10/CXCR3 Signaling in the DRG Exacerbates Neuropathic Pain in Mice - Yan-Fang Kong; Wei-Lin Sha; Xiao-Bo Wu; Lin-Xia Zhao; Ling-Jie Ma; Yong-Jing Gao (Neuroscience Bulletin, 2021)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Without insight accompanied with deteriorated brain functional alterations in healthy individuals with auditory verbal hallucinations: a pilot study - Chuanjun Zhuo; Feng Ji; Xiaodong Lin; Hongjun Tian; Lina Wang; Sha Liu; Hong Sang; Wenqiang Wang; Chunmian Chen (Brain Imaging and Behavior, 2020)
Few studies have reported on brain functional differences between healthy individuals with auditory verbal hallucinations (Hi-AVH) with and without insight, so we designed a study to address this knowledge gap. We enrolled 12 Hi-AVH with insight, 15 Hi-AVH without insight, and 15 AVH-free controls (Healthy controls). Global functional connectivity density (gFCD) mapping was used to estimate brain networks. We found that the most common alterations in both Hi-AVH groups were increased gFCD in superior parietal lobule and superior temporal gyrus. We also found that distinct brain functional patterns of Hi-AVH without insight comprised lower gFCD in the frontal lobe oculomotor area, dorsolateral prefrontal cortex, supramarginal gyrus, primary auditory cortex, sensorimotor cortex, ventral anterior, and posterior cingulate Our pilot findings support the hypothesis that abnormal reciprocal action in the circuits for processing perception, memory, language, and attentional control may be pathological features of auditory verbal hallucinations.

Emerging relationship between RNA helicases and autophagy - Miao-miao Zhao; Ru-sha Wang; Yan-lin Zhou; Zheng-gang Yang (Journal of Zhejiang University-SCIENCE B, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

A Simple Approach to the Toxicity Prediction of Anilines and Phenols Towards Aquatic Organisms - Jules Muhire; Bao Qiong Li; Hong Lin Zhai; Sha Sha Li; Jia Ying Mi (Archives of Environmental Contamination and Toxicology, 2020)

Microbiota analysis revealed vertical transmission and microbial adjusting function of symbiotic fungus in the attelabid weevil fungiculture - Bin Lin; Lin Wang; Muzammil Hussain; Xiaoling Zhang; Jianqing Tian; Sha Qi; Xingzhong Liu; Meichun Xiang (Science China Life Sciences, 2019)

Visualizing DC morphology and T cell motility to characterize DC-T cell encounters in mouse lymph nodes under mTOR inhibition - Qiaoya Lin; Zheng Liu; Meijie Luo; Hao Zheng; Sha Qiao; Chenlu Han; Deqiang Deng; Zhan Fan; Yafang Lu; Zhihong Zhang; Qingming Luo (Science China Life Sciences, 2019)

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

Comparative genomic analysis of the Lipase3 gene family in five plant species reveals distinct evolutionary origins - Dan Wang; Lin Zhang; JunFeng Hu; Dianshuai Gao; Xin Liu; Yan Sha (Genetica, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

Effect of grazing intensity on protozoan community, microbial biomass, and enzyme activity in an alpine meadow on the Tibetan Plateau - Bin Lin; Xiaorong Zhao; Yong Zheng; Sha Qi; Xingzhong Liu (Journal of Soils and Sediments, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Modeling farm nutrient flows in the North China Plain to reduce nutrient losses - Zhanqing Zhao; Zhaohai Bai; Sha Wei; Wenqi Ma; Mengru Wang; Carolien Kroeze; Lin Ma (Nutrient Cycling in Agroecosystems, 2017)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

Brain abnormalities in fucosidosis: transplantation or supportive therapy? - Minyan Jiang; Sha Liu; Hua Jiang; Yunting Lin; Yongxian Shao; Hao Hu; Xiaoyuan Zhao; Hongsheng Liu; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2017)

Pilot-Scale Study on Treating Wastewater from Magnesium-Based Exhaust Gas Cleaning System by a Novel Process - Tie Li; Lin Sha; Quan Liu; Jiao Zhao; Xiaojia Tang; Yimin Zhu (Water, Air, & Soil Pollution, 2017)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Different causes of photosynthetic decline and water status in different stages of girdling in Alhagi sparsifolia Shap. (Fabaceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Fan-jiang Zeng (Brazilian Journal of Botany, 2016)

How does habitat filtering affect the detection of conspecific and phylogenetic density dependence? - Junjie Wu; Nathan G. Swenson; Calum Brown; Caicai Zhang; Jie Yang; Xiuqin Ci; Jie Li; Liqing Sha; Min Cao; Luxiang Lin (Ecology, 2016)
Conspecific negative density dependence ( CNDD ) has been recognized as a key mechanism underlying species coexistence, especially in tropical forests. Recently, some studies have reported that seedling survival is also negatively correlated with the phylogenetic relatedness between neighbors and focal individuals, termed phylogenetic negative density dependence ( PNDD ). In contrast to CNDD or PNDD , shared habitat requirements between closely related individuals are thought to be a cause of observed positive effects of closely related neighbors, which may affect the strength and detectability of CNDD or PNDD . In order to investigate the relative importance of these mechanisms for tropical tree seedling survival, we used generalized linear mixed models to analyze how the survival of more than 10 000 seedlings of woody plant species related to neighborhood and habitat variables in a tropical rainforest in southwest China. By comparing models with and without habitat variables, we tested how habitat filtering affected the detection of CNDD and PNDD . The best‐fitting model suggested that CNDD and habitat filtering played key roles in seedling survival, but that, contrary to our expectations, phylogenetic positive density dependence ( PPDD ) had a distinct and important effect. While habitat filtering affected the detection of CNDD by decreasing its apparent strength, it did not explain the positive effects of closely related neighbors. Our results demonstrate that a failure to control for habitat variables and phylogenetic relationships may obscure the importance of conspecific and heterospecific neighbor densities for seedling survival.

Risk analysis and emergency actions for Hongshiyan barrier lake - Xingbo Zhou; Zuyu Chen; Shu Yu; Lin Wang; Gang Deng; Peijun Sha; Shouyi Li (Natural Hazards, 2015)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Peanut violaxanthin de-epoxidase alleviates the sensitivity of PSII photoinhibition to heat and high irradiance stress in transgenic tobacco - Sha Yang; De-Yun Meng; Lin-Lin Hou; Yan Li; Feng Guo; Jing-Jing Meng; Shu-Bo Wan; Xin-Guo Li (Plant Cell Reports, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Species diversity of myxomycetes associated with different terrestrial ecosystems, substrata (microhabitats) and environmental factors - Qi-Sha Liu; Shu-Zhen Yan; Shuang-Lin Chen (Mycological Progress, 2015)

Diversity of Endophytic Fungi Associated with the Foliar Tissue of a Hemi-Parasitic Plant Macrosolen cochinchinensis - Sheng-Liang Zhou; Shu-Zhen Yan; Qi-Sha Liu; Shuang-Lin Chen (Current Microbiology, 2015)

Expression and Localization of Estrogen Receptor in Human Breast Cancer and Its Clinical Significance - Lv Li; Qimin Wang; Xiupeng Lv; Lin Sha; Huamin Qin; Lifen Wang; Linlin Li (Cell Biochemistry and Biophysics, 2015)

Sorafenib Inhibition of Hepatic Stellate Cell Proliferation in Tumor Microenvironment of Hepatocellular Carcinoma: A Study of the Sorafenib Mechanisms - Zhi-min Geng; Rajiv Kumar Jha; Bo Li; Chen Chen; Wen-zhi Li; Jian-bao Zheng; Lin Wang; Sha Huanchen (Cell Biochemistry and Biophysics, 2014)

(−)-Epigallocatechin-3-Gallate Ameliorates Learning and Memory Deficits by Adjusting the Balance of TrkA/p75NTR Signaling in APP/PS1 Transgenic Mice - Mingyan Liu; Fujun Chen; Lei Sha; Shuang Wang; Lin Tao; Lutian Yao; Miao He; Zhimin Yao; Hang Liu; Zheng Zhu; Zhenjie Zhang; Zhihong Zheng; et al. (Molecular Neurobiology, 2014)

Photosystem II activity of typical desert plant Alhagi sparsifolia Sharp.: response to exposure to natural light after being kept in shade - Lei Li; Xiang-yi Li; Xin-wen Xu; Li-sha Lin; Fan-jiang Zeng; Feng-li Chen (Trees, 2014)

Effects of high temperature on the chlorophyll a fluorescence of Alhagi sparsifolia at the southern Taklamakan Desert - Lei Li; Xiang-Yi Li; Xin-Wen Xu; Li-Sha Lin; Fan-Jiang Zeng (Acta Physiologiae Plantarum, 2014)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Groundwater Risk Assessment of the Third Aquifer in Tianjin City, China - Donglin Dong; Wenjie Sun; Zhaochang Zhu; Sha Xi; Gang Lin (Water Resources Management, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Establishment and characterization of a new fish cell line from head kidney of half-smooth tongue sole (Cynoglossus semilaevis) - Yuan Zheng; Na Wang; Ming-Shu Xie; Zhen-Xia Sha; Song-Lin Chen (Fish Physiology and Biochemistry, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Late Triassic bivalves associated with a hydrothermal vent system in the Yidun Island Arc (SW China) of the eastern Tethys - Li Lin; LiDong Zhu; YanChun Pang; JinGeng Sha; Franz T. Fürsich; XiuGen Fu; XinLi Wang (Science China Earth Sciences, 2011)

A comparison of soil qualities of different revegetation types in the Loess Plateau, China - Chao Zhang; Sha Xue; Guo-Bin Liu; Zi-Lin Song (Plant and Soil, 2011)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

RGS22, a novel cancer/testis antigen, inhibits epithelial cell invasion and metastasis - Yanqiu Hu; Jun Xing; Lei Wang; Min Huang; Xuejiang Guo; Ling Chen; Min Lin; Yadong Zhou; Zhihua Liu; Zuomin Zhou; Jiahao Sha (Clinical & Experimental Metastasis, 2011)

Molecular cloning, characterization and expression of cDNA encoding translationally controlled tumor protein (TCTP) from Jatropha curcas L - Xiaobo Qin; Fan Gao; Jinping Zhang; Jihai Gao; Sha Lin; Yong Wang; Luding Jiang; Yi Liao; Lina Wang; Yongjiong Jia; Lin Tang; Ying Xu; et al. (Molecular Biology Reports, 2011)

Development and characterization of wheat-Psathyrostachys huashanica partial amphiploids for resistance to stripe rust - Yi Wang; Quan Xie; Kangyu Yu; Vaino Poysa; Lijuan Lin; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Biotechnology Letters, 2011)

Effects of livestock grazing intensity on soil biota in a semiarid steppe of Inner Mongolia - Sha Qi; Haixia Zheng; Qimei Lin; Guitong Li; Zhenhua Xi; Xiaorong Zhao (Plant and Soil, 2011)

Construction of Two BAC Libraries from Half-Smooth Tongue Sole Cynoglossus semilaevis and Identification of Clones Containing Candidate Sex-Determination Genes - Chang-Wei Shao; Song-Lin Chen; Chantel F. Scheuring; Jian-Yong Xu; Zhen-Xia Sha; Xiao-Li Dong; Hong-Bin Zhang (Marine Biotechnology, 2010)

Mechanism of the Specific Neuronal Toxicity of a Type I Ribosome-Inactivating Protein, Trichosanthin - Ou Sha; David Tai-Wai Yew; Eric Yu-Pang Cho; Tzi-Bun Ng; Lin Yuan; Wing-Hang Kwong (Neurotoxicity Research, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Isolation and characterization of 12 polymorphic microsatellite markers from ladyfish (Elops saurus Linnaeus) - Zhen-Xia Sha; Shi-Chao Xing; Chang-Wei Shao; Yong-Sheng Tian; Xiao-Lin Liao; Song-Lin Chen (Conservation Genetics, 2009)

Isolation and Characterization of a Curcin Promoter from Jatropha curcas L. and Its Regulation of Gene Expression in Transgenic Tobacco Plants - Xiaobo Qin; Jinping Zhang; Caixia Shao; Sha Lin; Luding Jiang; Shuwen Zhang; Ying Xu; Fang Chen (Plant Molecular Biology Reporter, 2009)

Artificial Gynogenesis and Sex Determination in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Yong-Sheng Tian; Jing-Feng Yang; Chang-Wei Shao; Xiang-Shan Ji; Jie-Ming Zhai; Xiao-Lin Liao; Zhi-Meng Zhuang; Peng-Zhi Su; Jian-Yong Xu; Zhen-Xia Sha; Peng-Fei Wu; et al. (Marine Biotechnology, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

A single residue mutation of 5-enoylpyruvylshikimate-3-phosphate synthase in Pseudomonas stutzeri enhances resistance to the herbicide glyphosate - Aimin Liang; Jiying Sha; Wei Lu; Ming Chen; Liang Li; Dan Jin; Yongliang Yan; Jin Wang; Shuzhen Ping; Wei Zhang; Yiding Wang; Min Lin (Biotechnology Letters, 2008)

Identification of a New Gene Encoding EPSPS with High Glyphosate Resistance from the Metagenomic Library - Dan Jin; Wei Lu; Shuzhen Ping; Wei Zhang; Jian Chen; Baoqing Dun; Ruiqiang Ma; Zhonglin Zhao; Jiying Sha; Liang Li; Zhirong Yang; Ming Chen; et al. (Current Microbiology, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

Molecular Cloning and Expression Analysis of the Myostatin Gene in Sea Perch (Lateolabrax japonicus) - Han-Qing Ye; Song-Lin Chen; Zhen-Xia Sha; Yang Liu (Marine Biotechnology, 2007)

Isolation of Female-Specific AFLP Markers and Molecular Identification of Genetic Sex in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Jing Li; Si-Ping Deng; Yong-Sheng Tian; Qing-Yin Wang; Zhi-Meng Zhuang; Zhen-Xia Sha; Jian-Yong Xu (Marine Biotechnology, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Defective expression of Gα12 in the testes of azoospermia patients and in the spermatozoa with low motility - Yanqiu Hu; Ying Lu; Zuomin Zhou; Yong Du; Jun Xing; Lei Wang; Min Lin; Jiahao Sha (Journal of Molecular Medicine, 2006)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)

Analysis of DNA methylation related to rice adult plant resistance to bacterial blight based on methylation-sensitive AFLP (MSAP) analysis - A.H. Sha; X.H. Lin; J.B. Huang; D.P. Zhang (Molecular Genetics and Genomics, 2005)

Differential expression of glucose-regulated protein 78 during spermatogenesis - Ran Huo; Ye-fei Zhu; Xiang Ma; Min Lin; Zuo-min Zhou; Jia-hao Sha (Cell and Tissue Research, 2004)